Lived experience of the elderly individuals living at home a phenomenological study. - Tabsing, Khristine H
The objective of this study was to interpret and understand the lived experiences of elderly living in the institution and elderly living at home. Five females and one male, aged between 69 and 87 years served as participants of the study. Three of the participants were from Asilo de Molo, an elderly institution, and the other three came from the municipality of Miagao. With Interpretative Phenomenological Analysis (IPA) as a lens, I gathered data by conducting in-depth interviews. The qualitative data obtained were then subjected to the four-step analysis prescribed by the IPA. The analysis revealed two major themes: the difficulties and the ways of coping of elderly individuals. These themes comprised experiences concerning physical, financial and spiritual aspects of elderly life. This study, however, had no inference that proved one home was better than the other. Grounding on the research findings, I generated insights that contribute to the extant literature on elderly experiences. I also discussed how cultural differences influenced the elderly individual?s lived word. With my study?s findings, I highlighted the need of policies to enhance the service and treatment provided institutions and families to elderly individuals.